"That's not who I am’: misrecognition, refusal and accommodation within parole - Werth, Robert (Punishment, probation and parole, 2024)
Drawing from interviews with individuals on parole, this chapter explores experiences of and responses to penal misrecognition. It documents that participants feel fundamentally misrecognised by the parole agency and penal state. They believe that the penal state views them as dangerous, defective and incapable of virtuous self-governance. Yet this is not how they perceive themselves. This leads to a delicate balancing act where participants refuse certain aspects of the penal state while accommodating others. On the one hand, individuals refuse parole’s misrecognition of them and reject the state’s authority to define who they are. On the other hand, they largely acquiesce to parole’s authority to supervise and regulate conduct. Turning to the concept of refusal highlights that individuals do not just attempt to resist penal power; rather, they flatly reject the state’s epistemic constructions. They do this by turning away from parole and by turning towards other forms of sociality beyond the penal state. This creates material and affective distance from parole and opens up space for self-recognition and for receiving positive recognition from others. In this way, individuals seek to minimise, move away from and/or bypass a penal intervention that is ostensibly designed to assist and support them.